Relationship between inflammation biomarkers, antioxidant vitamins, and bone mineral density in patients with metabolic syndrome - Lee, Yesong (The Korean Nutrition Society and the Korean Society of Community Nutrition, 2011)
Few studies have shown the correlation between metabolic syndrome and bone mineral density (BMD). The main pathogenic mechanisms of metabolic syndrome rely on chronic low-level inflammatory status and oxidative stress. There are few studies that examine the gender-specific effects of inflammation and antioxidants on BMD. In this study, we evaluated the relative contribution of these factors in patients with metabolic syndrome. We conducted a cross-sectional study of 67 men and 46 postmenopausal women with metabolic syndrome; metabolic syndrome was defined as having three or more metabolic syndrome risk factors. BMD, body fat mass, and lean body mass were evaluated. We also examined the levels of high sensitive C-reactive protein (hs-CRP), interleukin-6 (IL-6), adiponectin, vitamin E, and C in serum. Log-transformed hs-CRP levels were significantly higher in lumbar spine osteoporotic subjects than in normal subjects for women but not for men. There was no significant difference between the normal group and the osteoporotic group in other inflammatory markers. Stepwise regression analyses for BMD of the lumbar spine showed that lean body mass and vitamin E were significant determinants in men. Lean body mass and log-transformed hs-CRP were significant determinants in women Analysis for BMD of the femoral neck showed that lean body mass was a significant determinant for both men and women. There was no significant factor among the inflammatory markers or antioxidant vitamins affecting the femoral neck BMD for either gender. In conclusion, while hs-CRP is an independent predictor of the BMD of the lumbar spine in women, vitamin E showed profound effects on BMD in men but not women with metabolic syndrome.